Membangun Jiwa Kewirausahaan melalui Kurikulum Merdeka di TK Mumtaza Ceria Kalianyar Kertosono - Wathon, A (Lembaga Yasin AlSys, 2024)
Early childhood education is an important foundation in shaping children's character and skills, including an entrepreneurial spirit that is relevant to the demands of the 21st century. In the era of the Merdeka Curriculum, the development of an entrepreneurial spirit can be integrated into learning to encourage creativity, independence, and innovation from an early age. This study aims to identify the strategy and implementation of the Merdeka Curriculum in building an entrepreneurial spirit at Mumtaza Ceria Kindergarten, Kalianyar, Kertosono. This study uses a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with teachers, and documentation of learning activities. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that the implementation of the Merdeka Curriculum at Mumtaza Ceria Kindergarten was carried out through project-based activities, business simulation games, and exploration of the surrounding environment. Children are actively involved in activities such as making crafts, selling simple products, and role-playing as traders. The teacher acts as a facilitator who provides direction and supports children's exploration. This activity has been proven to be able to foster entrepreneurial values ​​such as the courage to take risks, creative thinking, and cooperation. In conclusion, the implementation of the Merdeka Curriculum in Mumtaza Ceria Kindergarten is effective in building an entrepreneurial spirit in early childhood. A flexible and activity-based curriculum provides space for the development of children's potential to the maximum. This study recommends further training for teachers and the development of entrepreneurship-based learning modules to support the sustainability of this program.